FIRM COMPETENCIES AND EXPORT PERFORMANCE: A STUDY OF SMALL AND MEDIUM MANUFACTURING EXPORTERS IN UGANDA - Kabagambe, Levi Bategeka; Ogutu, Martin; Munyoki, Justus M. (European Scientific Journal, ESJ, 2012)
In the exporting context, the notion of firm competencies entails processes by which organizational resources are developed, combined and transformed into value offerings for the export market. Despite the growing amount of academic exchange on competencies that underpin a firm’s export capability, there appears to be no unified framework for studying their effects on export performance (Freury & Freury, 2003). To address this gap, we draw on the Resources Based View and export marketing literature to develop a framework for the relationship between firm competencies and export performance. We empirically assess the predicted relationship using survey data from 76 small and medium manufacturing exporters in Uganda. Overall, our findings show that only marketing and sales competencies had significant positive effects on export performance. Surprisingly, the effect of production competencies on export performance, though significant was negative. From the results, export managers should outsource production to specialist firms and concentrate on marketing and sales activities in order to enhance export performance.